1994
DOI: 10.1007/bf00001305
|View full text |Cite
|
Sign up to set email alerts
|

Suspended particulate oxides and organic matter interactions in trace metal sorption reactions in a small urban river

Abstract: Abstract. The relative scavenging abilities of suspended particulate oxides (SPOX), and organic matter (SPOM) for Cd, Zn and Cu were evaluated in a small, anthropogenically influenced river. In addition, the factor most important in influencing the sorption density (A,: metal concentration associated with a given phase divided by the concentration of that geochemical phase in the suspended particulate pool) of each metal to SPOX and SPOM were identified through multiple linear regression analyses from the suit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…precipitate (the water is undersaturated), they are likely adsorbed onto the Fe-oxyhydroxides (ferrihydrite), which are known to have a high sorption capacity. Previous studies (Sholkovitz and Copland, 1981;Warren and Zimmerman, 1994) demonstrated that the adsorption of dissolved trace elements onto riverine suspended matter is a function of a number of variables, including the concentration of organic substances, suspended matter residence time, particle size and surface area, pH, Eh, T and source composition. The pH-Eh-T-conditions at which the red suspended matter and red sediments exist and the source composition are broadly similar (Table 1).…”
Section: Formation Of Red Suspended Matter and Red Sedimentmentioning
confidence: 99%
“…precipitate (the water is undersaturated), they are likely adsorbed onto the Fe-oxyhydroxides (ferrihydrite), which are known to have a high sorption capacity. Previous studies (Sholkovitz and Copland, 1981;Warren and Zimmerman, 1994) demonstrated that the adsorption of dissolved trace elements onto riverine suspended matter is a function of a number of variables, including the concentration of organic substances, suspended matter residence time, particle size and surface area, pH, Eh, T and source composition. The pH-Eh-T-conditions at which the red suspended matter and red sediments exist and the source composition are broadly similar (Table 1).…”
Section: Formation Of Red Suspended Matter and Red Sedimentmentioning
confidence: 99%
“…Overall DOM had a greater Cu adsorption density than FeOx, however trials adding particulate FeOx to DOM-complexed Cu showed FeOx was an effective scavenger, decreasing the proportion of Cu complexed to DOM. Alternate trials adding DOM to FeOx-sorbed Cu resulted in an increase in Cu sorption, suggesting FeOx-DOM complexation increased the system sorption capacity for Cu (Warren and Zimmerman 1994). Thus, HS incorporation in AMD treatment may result in an increased sorption capacity of precipitated hydroxides for some metals due to additional DOM complexation.…”
Section: Process Considerationsmentioning
confidence: 99%
“…Interactions between HS macromolecules via cationic bridges, polar interactions, hydrogen bonding or van der Waals forces may cause HS insolubility (Swift 1996), resulting in removal of HS complexed metals by sedimentation. Similar HS binding mechanisms may occur with precipitated metal hydroxide surfaces (Warren and Zimmerman 1994), resulting in adsorption of HS complexed metals to precipitates, and subsequent enhanced settling.…”
Section: Process Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Minerals, diatoms and other components of suspended particulate material (SPM) in the water columns of rivers, lakes and estuaries have the ability to bind dissolved trace metals, thereby reducing metal toxicity and influencing environmental fate. There are two principal agencies of dissolved metal removal by SPM; adsorption onto mineral or organic surfaces and biological uptake, particularly by diatoms and algae (e.g., Dzombak & Morel 1990;Warren & Zimmerman 1994;Tessier et al 1996). These removal processes need to be understood and quantified before reliable predictions can be made concerning the extent to which metal toxicity will be reduced, and/or metals will accumulate in the sediments, in a natural aquatic system.…”
Section: Introductionmentioning
confidence: 98%